EP241 Role of no further treatment after radical hysterectomy in early stage cervical cancer with intermediate risk factors. (1st November 2019) - Akilli, H; Aksoy Karakaş, L; Nihan, H; Esra, K; Ayhan, A
Abstract : Introduction/Background: Radical hysterectomy plus pelvic +- paraaortic lymhadenectomy is the first choice of treatment in early stage cervical cancer and adjuvant treatment is determined according to risk factors.High risk patients (positive surgical margine, positive parametrial invasion, lyph node invoılvement) recieve adjuvant chemoradiotherapy without a doubt.However adjuvant treatment in patients with intermadiate risk factors (tm size ≥4 cm, positive LVSİ and with deep stromal invasion) remains controversial. ESGO, ESTRO and ESP recomend adjuvant radiotheraphy to patients with these risk factors and also offer observation as an option especialy with an experienced team. Methodology: This retrospective cohort study was carried out in Baskent University School of medicine Ankara, Turkey. All patietns underwent radical hysterectomy plus pelvic ±paraaortic lymhadenectomy, casese were included with negative lyph node, negative parametrial invasion and negative surgical margine. Patients with positive LVSİ and Deep stromal İnvasion or LVSİ and tm size ≥4 cm or DSİ and tm size ≥4 cm or only tm size ≥4 cm with minimum 24 months of follow up time were enrolled. Results: T he median age of patients were 50, 4 years (23–80 y). 66 patients were treated only with surgery and 68 with adjuvant radiotheraphy after surgery. Total recurrence rates were 16, 6% vs 23, 5% respectively p=0, 9. Besides each group had similar local recurrence rates.Five year DFS were 80, 2% vs 78, 2% in no adjuvant treatment and radiotheraphy group respectivelly p=0, 25.Fİve year OS were 86% and 88% p=0, 57. Having tumor size ≥4 cm was found to the only independent factor for recurrence HR 2, 426 (1, 123–5, 239 with 95, 0 Cİ). Conclusion: No further treatment after radical surgery for early stage cervical carcinoma with intermediate risk factors is a good option with same oncologic outcomes. Disclosure: Nothing to disclose.